For democracy: Planning and publics without the state. (November 2016) - Purcell, Mark
This article argues that planning should develop a robust conception of "publics without the State." We should do so because the State is a necessarily oligarchical arrangement that prevents us from achieving real democracy. We should explore publics without the State in both theory and practice.